Peranan Kapal Tol Laut dalam Menunjang Distribusi Logistik pada Daerah Tertinggal oleh PT. Subsea Lintas Globalindo Cabang Tanjung Perak Surabaya - Lias Epindo Ginting; Dirhamsyah Dirhamsyah; Muhammad Sahid (KALAO'S MARITIME JOURNAL, 2025)
The purpose of writing this paper is to find out the role of sea toll ships in supporting logistics distribution in disadvantaged areas by PT. Subsea Lintas Globalindo Tanjung Perak Surabaya branch. The methods used in data collection are the field method through observation, as well as the library research method, to understand the extent of the sea toll ship operated by PT. Subsea Lintas Globalindo Tanjung Perak Surabaya Branch contributes to smoothing the flow of logistics distribution to disadvantaged areas, especially in Eastern Indonesia. The results of the study show that sea toll ships play a strategic role in reducing the disparity in the price of goods, increasing logistics accessibility, and supporting equitable development and economic growth in remote areas. The obstacles faced include uncertain weather factors, limited port infrastructure, and coordination that still needs to be strengthened between related institutions. Therefore, better synergy is needed between the government, ship operators, and other stakeholders, including the private sector and local communities, to optimize the benefits of the sea toll program in a sustainable manner, improve distribution efficiency, and support equitable distribution of welfare throughout Indonesia.